A comparative whole genome sequencing analysis identified a candidate locus for lack of operculum in cultivated gilthead seabream (Sparus aurata). (20th February 2021) - Bertolini, F.; Ribani, A.; Capoccioni, F.; Buttazzoni, L.; Utzeri, V. J.; Bovo, S.; Schiavo, G.; Caggiano, M.; Rothschild, M. F.; Fontanesi, L.
Summary: The gilthead seabream ( Sparus aurata, Sparidae family) is commonly used for aquaculture. Despite its great economic value, several problems in its cultivation remain. One of the major concerns is the high frequency of morphological abnormalities occurring during the early developmental stages. Partial and/or total lack of operculum is the most frequent anomaly affecting the fish cranial region. The existence of genetic factors that can at least partially determine this defect has been hypothesized. In this work, two DNA pools of highly related fry, one composed of normal‐looking (control) fish and the other lacking an operculum (case), were constructed and whole‐genome resequencing data produced from the two were compared. The analysis revealed a 1 Mb region on chromosome 2 with higher heterozygosity in the lack of operculum DNA pool than in the control DNA pool, consistent with the enrichment, in the first DNA pool, of one or more haplotypes causing or predisposing to the defect together with other normal haplotypes. A window‐based F ST analysis between the two DNA pools indicated that the same region had the highest divergence score. This region contained 2921 SNVs, 10 of which, with predicted high impacts (three splice donor and seven stop‐gained variants), were detected in novel genes that are homologous to calcium‐sensing receptor‐like genes, probably involved in bone development. Other studies are needed to clarify the genetic mechanisms involved in predisposing fry to this deformity and then to identify associated markers that could be used in breeding programs to reduce the frequency of this defect in the broodstock.